Identification of Interacting Hot Spots in the β3 Integrin Stalk Using Comprehensive Interface Design - Donald, Jason E. (American Society for Biochemistry and Molecular Biology, 2010)
Protein-protein interfaces are usually large and complementary surfaces, but specific side chains, representing energetic “hot spots,” often contribute disproportionately to binding free energy. We used a computational method, comprehensive interface design, to identify hot spots in the interface between the stalk regions of the β3 and the complementary αIIb and αv integrin subunits. Using the Rosetta alanine-scanning and design algorithms to predict destabilizing, stabilizing, and neutral mutations in the β3 region extending from residues Lys(532) through Gly(690), we predicted eight alanine mutations that would destabilize the αIIbβ3 interface as well as nine predicted to destabilize the αvβ3 interface, by at least 0.3 kcal/mol. The mutations were widely and unevenly distributed, with four between residues 552 and 563 and five between 590 and 610, but none between 565 and 589, and 611 and 655. Further, mutations destabilizing the αvβ3 and αIIbβ3 interfaces were not identical. The predictions were then tested by introducing selected mutations into the full-length integrins expressed in Chinese hamster ovary cells. Five mutations predicted to destabilize αIIb and β3 caused fibrinogen binding to αIIbβ3, whereas three of four predicted to be neutral or stabilizing did not. Conversely, a mutation predicted to destabilize αvβ3, but not αIIbβ3 (D552A), caused osteopontin binding to αvβ3, but not fibrinogen binding to αIIbβ3. These results indicate that stability of the distal stalk interface is involved in constraining integrins in stable, inactive conformations. Further, they demonstrate the ability of comprehensive interface design to identify functionally significant integrin mutations.